Romantic Meaning of Khalil Gibran’s Poetry (Hermeneutical Approach) - Yakin, Lukman Ainul (Critical Review of English-Arabic World Journal, 2022)
This study explores the Kahlil Gibran’s poetry using the hermeneutical approach. This study aims (1) to examine the intrinsic elements of his poetry and (2)to explain the romantic meaning in his poetry. The scope of this study covers seven poems of Khalil Gibran. All romantic words and meanings could be used as the data. The hermeneutic approach requires interpretation. The meaning of the poetry is influenced by each reader's perceptions of knowledge and experience, environment factor, the perspective or dimension of their interest, and other extrinsic factors. The first to the seventh poem shows that Khalil Gibran often uses the word love related to the romantic meaning. It is also based on Khalil Gibran's biography of his life. It tells about his love, live and life.